Unattended Ground, Sea, and Air Sensor Technologies and Applications XIV 2012
DOI: 10.1117/12.918582
|View full text |Cite
|
Sign up to set email alerts
|

Automatic human action recognition in a scene from visual inputs

Abstract: Surveillance is normally performed by humans, since it requires visual intelligence. However, this can be dull and dangerous, especially for military operations. Therefore, unmanned autonomous visual-intelligence systems are desired. In this paper, we present a novel system that can recognize human actions, which are relevant to detect operationally significant activity. Central to the system is a break-down of high-level perceptual concepts (verbs) in simpler observable events. The system is trained on 3482 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Although [13] already showed that the RF TP is a good stand alone verb classifier, here we see it also performs well when applied to a description task. Even though the RF TP classifier is not optimized for the description generator (e.g.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Although [13] already showed that the RF TP is a good stand alone verb classifier, here we see it also performs well when applied to a description task. Even though the RF TP classifier is not optimized for the description generator (e.g.…”
Section: Resultsmentioning
confidence: 91%
“…This overall system is described in [12,13] and it is summarized here. It consists of five building blocks (see figure 2): visual processing, fusion engine, event description, action classifier, and the description generator.…”
Section: System Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work may include a large scale experiment, the combination with behavioral profiling [6] or automatic action recognition [5][7] [9], and an evaluation on a public available database for multi-camera surveillance for person reidentification, such as the database of Bialkowski e.a. [2].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A person-tracing system is composed of multiple components such as moving object detection [13] or static person detection [9][15] [26], segmentation, tracking [25] [43][45] [46], human interaction [6] [8] and person re-identification. The scope of our investigation focuses on the person re-identification algorithm which uses still images of the persons' bounding boxes as input and performs two steps: descriptor computation and matching ( Figure 1).…”
Section: Literature Overviewmentioning
confidence: 99%